CHEMICAL ANALYSIS DENDROCALAMUS ASPER BAMBOO AND SUITABILITY FOR PULP AND PAPER - M. Faizal Esa, M. Faizal Esa; Nor Mazlana Main, Nor Mazlana Main; M. Nazrul Roslan, M. Nazrul Roslan; Latifah Jasmani, Latifah Jasmani; Khairu Kamarudin, Khairu Kamarudin (2023)
The chemical analysis of bamboo species, namely Dendrocalamusasper or popular named as BuluhBetong has been evaluated. From the age of 3 years, this species shows different chemical properties related to holocellulose,  cellulose, solvent extraction, alkali solubility, lignin, hot water solubility, cold water solubility, ash, silica and pentosan. Holocellulose content of about 60.48% to 64.75%,  cellulose content of about 35.73% to 43.14%, for all bamboo segments indicated as a suitable material for pulp and papermaking. Low level of solvent extractive of about 5.09% to 6.23%, hot water soluble of about 6.29% 9.49% and cold water soluble of about 9.35% to 10.49% also produced the content that cannot interfere with the paper-making process. In addition, the low ash and silica content for all sections of bamboo will indicate a normal alkali consumption and give little challenge to the operational process. High pentosan content in the middle and top sections between 16.32% and 20.88% and lignin content of around 39.27% to 32.51% also promise little challenge for pulping as compared to the bottom section. Therefore, based on the overall findings, the middle section, and the top section had an advantage over the bottom section. As a result, the middle and top sections are best used as a new material in pulp and paper making process.